State, Traditional Authorities and Political Legitimacy: the parameters of a ‘marriage of convenience’ in Mandlakazi - Lourenço, Vitor Alexandre Antunes (2016)
It is commonly accepted that the current process of «political modernization» in Mozambique has given increased visibility and importance to the problems concerningthe relationship between State and the Traditional Authorities.In face of the resilience of Traditional Authorities as mediation agencies between the present and the past, the State cannot afford to ignore their presence in the political landscape. The picture is rather complex: however predominantlybased on a modern political apparatus, the State also tries to include the Traditional Authorities under its umbrella, thus seeking to benefit both from «modern» and «traditional» political legitimization. Traditional Authorities, on the other hand, while fighting to keep control over their communities on their own terms, are nevertheless eager to capture some of the State resources, to increase their ability to maintainthe old ruling patterns, based on the existence of a clientelist network nurtured through the redistribution of wealth and positions of power.